Ice-nucleating particle concentration impacts cloud properties over Dronning Maud Land, East Antarctica, in COSMO-CLM2 - F. Sauerland; N. Souverijns; A. Possner; H. Wex; P. Van Overmeiren; A. Mangold; K. Van Weverberg; K. Van Weverberg; N. van Lipzig (Atmospheric Chemistry and Physics)
Ice-nucleating particles (INPs) have an important function in the freezing of clouds but are rare in East Antarctica. At the Belgian Princess Elisabeth Antarctica station, immersion freezing INP concentrations between 6×10-6<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="6ce2bd4a2453ff1f01ee11c1b9313333"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-13751-2024-ie00001.svg" width="42pt" height="14pt" src="acp-24-13751-2024-ie00001.png"/></svg:svg> and 5×10-3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="0e05550f1fe703b9e5d4004578344828"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-13751-2024-ie00002.svg" width="42pt" height="14pt" src="acp-24-13751-2024-ie00002.png"/></svg:svg> L−1 have been observed with an activation temperature of −20 °C. These low concentrations offer a possible explanation for the occurrence of supercooled liquid water in clouds observed using the station's micro rain radar and ceilometer. We used the model of the Consortium for Small-scale Modeling (COSMO) in climate mode (CLM) coupled to the Community Land Model (CLM) (COSMO-CLM2) with an added aerosol-cycle module to test the cloud phase's sensitivity in response to varying prescribed INP concentrations. We tested two cases, one in austral summer and one in austral winter, and analysed the differences resulting from INP concentration changes for an area around the station and over the Southern Ocean within the selected domain. Our results show a strong influence of the INP concentration on the liquid water path in both regions, with higher concentrations reducing the amount of liquid water. Over the Southern Ocean, this effect is stronger during winter: during summer, a significant portion of water remains in liquid state regardless of INP concentration. Over the continent, this effect is stronger during summer: temperatures in winter frequently fall below −37 °C, allowing homogeneous freezing. The largest increase in the liquid water fraction of total cloud hydrometeor mass is simulated over the Southern Ocean in winter, from 9.8 % in the highest tested INP concentration to 50.3 % in the lowest. The radiative effects caused by the INP concentration changes are small, with less than 3 W m−2 difference in the averages between different concentrations.